Epithelioid trophoblastic tumor - Sevinc Hallac Keser; Sermin Coban Kokten; Caglar Cakir; Sibel Sensu; Esra Esim Buyukbayrak; Nimet Karadayi (Elsevier, 2015)
Objective: To describe a case of epithelioid trophoblastic tumor (ETT) in a postmenopausal woman, which had several peculiar features that differentiate it from previously reported ETTs. Case report: ETT of the uterus is a rare form of trophoblastic tumor with only 100 cases distinguished until now. Our case differs from the previously reported ones due to its several exceptional features. Our patient had no history of trophoblastic or gynecological disease; is postmenopausal; had endocervical extension from the beginning; recurrences and metastasis at follow up; and had a high Ki-67 index and a normal beta-human chorionic gonadotropin value. Conclusion: Because precise differential diagnosis will alter the therapeutic approach and prognosis, it is necessary for treating physicians to be aware of these unusual presentations.